2017
DOI: 10.1089/zeb.2017.1453
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Stimulates the Onset of Adult Feeding Kinematics in Zebrafish

Abstract: The physical demands for swimming and feeding change dramatically over the course of development for many aquatic animals. Indeed, in teleosts, the transition from larva to adult involves major shifts in both trophic morphology and feeding behavior. A spike in thyroid hormone (TH) coordinates many developmental processes that occur during this adult transition in numerous vertebrate species. Using mutant and transgenic zebrafish, we tested the hypothesis that TH is essential for the transition from larval to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…This decoupling may indicate the timing of the metamorphosis of A. ocellaris, which would be mainly characterized by pigmentation changes and not by drastic morphological changes, as it has been observed in grouper, flatfish, or surgeonfish. 8,11,74 In those species, it is known that thyroid hormones are controlling metamorphosis as in amphibians, 75 and it has been shown that these hormones markedly affect overall growth and development rates, as well as individual traits including pigmentation and scales, 76 feeding kinematics, 77 and morphometrics and the lateral line. 78 It is similarly likely that thyroid hormones control the morphological and pigmentation changes that occur during A. ocellaris metamorphosis.…”
Section: Dissociation Between Morphological and Pigmentation Changesmentioning
confidence: 99%
“…This decoupling may indicate the timing of the metamorphosis of A. ocellaris, which would be mainly characterized by pigmentation changes and not by drastic morphological changes, as it has been observed in grouper, flatfish, or surgeonfish. 8,11,74 In those species, it is known that thyroid hormones are controlling metamorphosis as in amphibians, 75 and it has been shown that these hormones markedly affect overall growth and development rates, as well as individual traits including pigmentation and scales, 76 feeding kinematics, 77 and morphometrics and the lateral line. 78 It is similarly likely that thyroid hormones control the morphological and pigmentation changes that occur during A. ocellaris metamorphosis.…”
Section: Dissociation Between Morphological and Pigmentation Changesmentioning
confidence: 99%
“…Danionellas are Danionins relatively closely related to zebrafish (McCluskey and Postlethwait 2014). Members of this miniaturized group are developmentally arrested and resemble larval Danios in several ways: adult Danionellas lack scales, barbels and many typically late-ossifying bones (Britz, Conway et al 2009, Britz andConway 2016), and they retain a larva-like pigment pattern and feeding kinematics (McMenamin, Carter et al 2017, Galindo, Sweet et al 2018. Danionellas are emerging as a novel model for studying behavior, neurobiology and brain function (Penalva, Bedke et al 2018, Schulze, Henninger et al 2018, and a hybrid genome assembly was recently completed (Kadobianskyi, Schulze et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…T 3 has a pleiotropic effect and influences numerous target genes (Rastorguev et al, 2016;Viguerie & Langin, 2003). TH is known to influence timing and rate of multiple developmental events in fish (Blanton & Specker 2007;Brown, 1997;de Jesus, Toledo, & Simpas, 1998;Guillot et al, 2016;Janz, 2000;McMenamin & Parichy, 2013;McMenamin, Carter, & Cooper, 2017;Parichy, Reedy, & Erickson, 2006;Shkil, Kapitanova, Borisov, Abdissa, & Smirnov, 2012;Singh & Nüsslein-Volhard, 2015), including pigment pattern development (Guillot et al, 2016;Jegstrup & Rosenkilde, 2003;McMenamin et al, 2014;Prazdnikov & Shkil, 2016;Yoo, Takeuchi, Tagawa, & Seikai, 2000). Thus, manipulation of TH status is an appropriate method to test the hypothetical role of heterochronies in the formation of cichlid pigment pattern diversity.…”
mentioning
confidence: 99%